A câmara de nuvens: de objeto científico à prática pedagógica de Física Moderna - Rodrigues, Mateus Miranda (2025)
By Material Culture it is understood that objects carry historical meanings and attributes, and that through a detailed description we are able to expand our historical sources without being restricted only to written documents. In this sense, studies of material culture began to be inserted in the history of science through investigations of scientific instruments. In this way, scientific material culture emerges, intended for the analysis of two categories of instruments, those used in research (scientific objects) and those intended for teaching laboratories (pedagogical objects). In higher education, specifically in teaching laboratories, there is a very fine line between the meaning of each category. When dealing with Modern Physics, in which phenomena and objects are a black box, understood based on preconceived theoretical models, experimental practice becomes just a demonstration and loses its initial investigative character, so the instruments pass to be, predominantly, for pedagogical and demonstrative purposes. Thus, through a case study, this work aims to investigate the cloud chamber, taking into account the historical and epistemological aspects used in its construction and all the adaptations undergone until its arrival in the teaching laboratories. In doing so, in the following way: review in a historiographical way the scientific versions of the chamber of clouds; analyze the pedagogical version of the cloud chamber based on the scientific material culture approach; identify the factors that made the cloud chamber a pedagogical object and the importance of this instrument in Science Teaching. The first versions of the cloud chamber are classified as scientific objects, as their purpose was to study the phenomenology of subatomic particles. However, over the years, the chamber undergoes modifications and becomes increasingly compact, soon losing its investigative character and becoming an object of pedagogical and publicity nature. Furthermore, the way in which the cloud chamber is used in laboratories distorts it, as in many cases the experiments worked on are already scripted, with only a brief experimental visualization followed by data collection. Thus, we can conclude that the cloud chamber is a fundamental piece of equipment in teaching laboratories, as it allows students to have a good understanding of physical phenomena. However, considering its historicity, it is underused, attributing a distorted empirical character to the knowledge acquired at the end of the 19th century and beginning of the 20th century, which is Modern Physics.